Dinamika Komunikasi Dalam Circle Pertemanan Di Kalangan Mahasiswa UIN Raden Fatah Palembang - Sumartina, Azizah Ar Rokia; Henny Yusalia; M. Mifta Farid (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study aims to identify and describe the dynamics of communication in the friendship circle of UIN Raden Fatah Palembang students. In this study, the author uses a qualitative approach method with observation techniques and in-depth interviews with students from several faculties and documentation. The theory used in this study is the communication network theory from Everet M. Rogers to analyze the role of social structure in student friendship circles. The results of the study show that friendship circles are formed due to similarities in activities, interests, and backgrounds. Communication in the circle is dominated by direct and digital communication, with various central roles such as opinion leaders and connectors. Factors such as social hierarchy, digital media, and communication misunderstandings are the main challenges in interactions betweenstudents.